PENGARUH KOMPENSASI, KOMUNIKASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI KANTOR BADAN PERTANAHAN NEGARA (BPN) KABUPATEN BANDUNG - Nabila, Hasna Lutfiyyah; Recky, Recky; Saputro, Arie Hendra (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the influence of the independent variables: compensation, communication, and work discipline, on the dependent variable: performance, using multiple linear regression. The results indicate that only the work discipline variable is partially significant, with a significance value of 0.006, while compensation (0.240) and communication (0.586) do not significantly contribute to performance. These findings align with previous research highlighting the importance of work discipline as a key factor in influencing performance. On the other hand, the insignificance of compensation and communication suggests the need for further evaluation regarding the relevance or quality of measurement for these two variables. This study concludes that the primary focus in improving performance should be directed at managing work discipline, while additional exploration is required to identify other relevant variables. These results provide valuable insights for policymakers and researchers to better understand the dynamics of relationships between variables in the relevant context. Keywords: Compensation, Communication, Work Discipline, Performance